2018
DOI: 10.1111/jphp.12841
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-apoptotic effects of the combination of Ligusticum chuanxiong and Radix Paeoniae against focal cerebral ischaemia via TLR4/MyD88/MAPK/NF-κB signalling pathway in MCAO rats

Abstract: XS could protect MCAO rats by anti-inflammation and anti-apoptosis through TLR4/MyD88/MAPK/NF-κB signalling pathway. Furthermore, the combination has a more meaningful improvement on focal cerebral ischaemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…It has been reported that the NF-κB and MAPK signaling pathways accelerate the inflammatory process in cerebral ischemia-reperfusion injury [32][33][34]. This process is consistent with the inflammatory response signaling pathway that is induced by LPS.…”
Section: Ala Alleviated Cerebral Ischemia-reperfusion Injury In the Msupporting
confidence: 78%
“…It has been reported that the NF-κB and MAPK signaling pathways accelerate the inflammatory process in cerebral ischemia-reperfusion injury [32][33][34]. This process is consistent with the inflammatory response signaling pathway that is induced by LPS.…”
Section: Ala Alleviated Cerebral Ischemia-reperfusion Injury In the Msupporting
confidence: 78%
“…The Lf-induced decrease in TLR-4 level, in the current study, could be attributed to the fact that Lf has anti-inflammatory as well as anti-oxidative properties [ 50 , 51 ], which was evident by the restoration of SOD and NrF2 levels towards normal values, with a statistically significant difference from the control group. The Lf-induced modulation of the TLR-4 pathway and the pro-inflammatory cascade, via inhibition of reactive oxygen species generation and through the direct use of anti-inflammatory agents, was previously reported [ 52 ]. Similarly, and at the cellular level, Lf was shown to modulate differentiation, activation, migration, proliferation, and functions of immune cells using the signaling pathways, NF-κB and MAPK [ 53 ].…”
Section: Discussionmentioning
confidence: 97%
“…The data suggest that OMT administration may protect against LPS-induced ALI in vivo and in vitro by inhibiting the JNK signaling pathway. Toll-like receptor 4 (TLR4) can recognize and interact with LPS and subsequently activate the downstream MAPK pathways, eventually leading to an inflammatory response [ 12 , 15 ]. Previous studies reported that LPS-induced ALI can be attenuated by other drugs through the TLR4-mediated MAPK pathway [ 16 , 33 ].…”
Section: Discussionmentioning
confidence: 99%